VD_FINDINFO Décision / 2013 / 1074 vom 23. Dezember 2013 - VD Tribunal cantonal (2013)
CLASSEMENT DE LA PROCÉDURE, FRAIS DE LA PROCÉDURE, PLAIGNANT | 319 CPP (CH), 393 al. 1 let. a CPP (CH), 395 let. b CPP (CH), 427 al. 2 CPP (CH)